1 THE PUBLIC RECORDS OF THE COLONY OF CONNECTICUT 95–96 (J. Hammond Trumbull ed. 1850) (enacted 1643 - (:unkn) unknown (General Publisher, 1643)
Required each family to bring arms to church every Sabbath and lecture day.
--
Keywords: REQUIRED POSSESSION